Mercado de almas aflitas: crime, castigo e conversão religiosa. - Araújo, Fábio Firmino de (2009)
This study concerns to a theoretical and field research to understand the symbolic and political strategies of religious conversion to evangelical churches in social subjects marked their stories of life in the practice, criminal careers and prospects. The social actors investigated here are prisoners of the Maximum Security Criminalist Penitentiary Geraldo Beltrão, located in the district of Mangabeira VI, in João Pessoa, State of Paraíba. Our goal is to demonstrate the impact of religious conversion in the process of regeneration, recovery and social re-inclusion of prisioners in the society of origin, before the current prison system. We try to identify the prison population as fertile ground for religious proselytism neopentecostal. Also we presented the report of a cult in prison, where trying to analyze how the celebrations held by prisoners and religious experience in everyday life imprisonment.